Crime, punishment, and mental illness : law and the behavioral sciences in conflict - Erickson, Patricia E., 1947- (Critical issues in crime and society., 2008)
Hundreds of thousands of the inmates who populate the nation?s jails and prison systems today are identified as mentally ill. Many experts point to the deinstitutionalization of mental hospitals in the 1960s, which led to more patients living on their own, as the reason for this high rate of incarceration. But this explanation does not justify why our society has chosen to treat these people with punitive measures. In Crime, Punishment, and Mental Illness, Patricia E. Erickson and Steven K. Erickson explore how societal beliefs about free will and moral responsibility have shaped current polic.